Attacks on security goals (confidentiality, integrity, availability) in VANET: A survey - Sumra, I.A. (Springer Verlag, 2015)
In recent years, the VANET has received a greater attention among researchers in academia and industry due to its potential safety application and nonsafety application. Malicious users are one of the types of attackers in VANET and create the security problems. Confidentiality, integrity and availability (CIA) are major components of security goals. The increasing research interest, potential applications, and security problem in VANET lead to the needs to review the attacks on security goals. In this paper, the aim is to present the survey of attacks on security goals and to describe in details the nature of attacks and the behaviour of attackers through different scenarios in the network. The paper also provides a better understanding of security goals and finally it provides an analysis and classifies the attacks on the basis of security goals into different threat levels that can help in the implementation of VANET in real life. Â© Springer Science+Business Media Singapore 2015.